Cancer phototherapy by CO releasing terpyridine-based Re(i) tricarbonyl complexes via ROS generation and NADH oxidation - Kushwaha R.; Upadhyay A.; Saha S.; Yadav A.K.; Bera A.; Dutta A.; Banerjee S. (My University, 2025)
Here, we have synthesized and characterized three visible light responsive terpyridine based-Re(i)-tricarbonyl complexes; [Re(CO)3(ph-tpy)Cl] (Retp1), [Re(CO)3(an-tpy)Cl] (Retp2), and [Re(CO)3(py-tpy)Cl] (Retp3) where ph-tpy = 4′-phenyl-2,2′:6′,2″-terpyridine; an-tpy = 4′-anthracenyl-2,2′:6′,2″-terpyridine, py-tpy = 4′-pyrenyl-2,2′:6′,2″-terpyridine. The structures of Retp1 and Retp2 were confirmed from the SC-XRD data, indicating distorted octahedral structures. Unlike traditional PDT agents, these complexes generated reactive oxygen species (ROS) via type I and type II pathways and oxidized redox crucial NADH (reduced nicotinamide adenine dinucleotide) upon visible light exposure. Retp3 showed significant mitochondrial localization and demonstrated photoactivated anticancer activity (IC50 ∼ 2 µM) by inducing ROS-mediated cell death in cancer cells selectively (photocytotoxicity Index, PI > 28) upon compromising mitochondrial function in A549 cells. Their diagnostic capabilities were ultimately assessed using clinically relevant 3D multicellular tumor spheroids (MCTs). © 2024 The Royal Society of Chemistry.